Musical figuring of postcolonial urban segmentarity in Wasiu Ayinde's fuji works (2016)
In this paper, I gleaned from Gilles Deleuze and Felix Guattari’s concept of segmentarity to examine the how postcolonial urban forms of social segregation and marginalization are figured in selected musical works of WasiuAyinde - a prominent fujimusician.The study adopted semi ethnographic design. Purposive sampling technique was used to select two tracks from different albums by Wasiu Ayinde, namely, ‘Kl’on the album Fact and ‘Action Congress’on the album Promising, where the artiste portrays the challenge of urban social conditions such as poverty, unemployment, epileptic power supply and so forth which are largely stratified along class distinction. In the work - Fact – Ayinde represents his criticism of the type of maladministration that characterized President Obasanjo's civilian regime between 1999 and 2007, particularly the ruler's failure in redressing inequality and the widening segregations between different classes of people. I argue that although the musician shows a strong desire to eliminate this postcolonial urban segmentarity and marginality, he, nevertheless, also performatively participates in maintaining and reproducing it. This is based on the musician's ambiguous responses to similar conditions, especially when viewed against his eulogy of, and collaboration with the then major opposition political party, Action Congress, widely criticized for its ineptitude in political governance.